High-resolution Holocene Glacial Chronologies across Patagonia (47 -51 S): Testing mechanisms of Initiation and modulation of the glacial events in the southern Andes - (:unkn) unknown (My University, 2025)
Glacial fluctuations have been used to reconstruct past climate variability in most of the mountain regions around the world. A well-resolved glacial chronology is crucial to compare sequences of glacial/climate events within and between regions, and thus, to unravel mechanisms underlying past climate changes at different time and spatial scales. Important efforts have been made towards unraveling the Holocene climate evolution of the Southern Andes; however, the timing, patterns and causes of glacial fluctuations during this period, still remain elusive. This proposal aims to reconstruct the history of glacial fluctuations for selected small climate-sensitive mountain glaciers in southern South America (47°-51°S) during the Holocene, a period within recent earthy history for which there remain large discrepancies in our interpretation of the geological record. We will combine geomorphology, stratigraphy, and geochronology to document the spatial and temporal structure of Holocene glacial changes in central and southern Patagonia. In order to overcome the limitations of the commonly used dating techniques, we propose to combine different dating methods: dendrochronology, terrestrial cosmogenic nuclide surface exposure dating, and radiocarbon dating. By combining these approaches, we expect to establish high-resolution glacial chronologies that allow us not only to decipher the timing and structure of fluctuations of the study glaciers, but also to test mechanisms involved in the initiation and modulation of the magnitude of glacial events in Patagonia during the Holocene. Considering the predicted scenarios of anthropogenic-induced climate change, we suggest that this research is relevant and transcends far beyond pure academic interests, since it will (i) contribute to our understanding of natural climate variability under interglacial conditions; (ii) provide a baseline to assess present-day glacier fluctuations; and (iii) provide new insights regarding the mechanisms underlying glacial fluctuations.